Analysis Application of Average Effective Rate (TER) In Regulation No. 58 of 2023 and its Implications - Indah Kurniyawati (Journal of Economics and Business (JECOMBI), 2025)
The Indonesian government issued Government Regulation No. 58 of 2023 as a form of updating the mechanism for deducting Income Tax (PPh) Article 21 through the application of the Average Effective Rate (TER). This study aims to analyze the advantages and implications of applying TER on simplifying tax administration and increasing taxpayer compliance. The methods used are descriptive and explanatory qualitative, with data collection techniques including literature review and simulation of PPh 21 calculations based on PTKP categories. The results of the study indicate that the TER scheme can provide certainty and stability in monthly tax withholding, as well as reduce the burden of annual reconciliation. Additionally, first-quarter 2024 data shows a significant increase in PPh 21 revenue, reflecting the positive impact of this policy on compliance. However, challenges remain, particularly in tax literacy and system adaptation in the informal sector. Therefore, broader education and technological support are needed to ensure the equitable and optimal implementation of TER.